Some aspects of turn-taking in dialogs of Polish and German youths. Presented on the example of task oriented dialogs - Woźniak, Miłosz (Glottodidactica, 2020)
The aim of this paper is to discuss the role of turn-taking in dialogs of Polish and German schoolchildren aged from 13 to 15 years. The paper begins by describing the project and briefly viewing the most relevant definitions (e. g. turn, backchannels, segments). The next section presents the notation system and the methods. The samples were selected from the BORDERLAND data bank and, in total, they included nine pairs and over 1,000 segments. On this basis, it can be concluded that turn-taking in uniform pairs (Polish-Polish and German-German) is more defensive, and that the interlocutors tend to use more segments. There might also be a slight tendency for Polish speakers to interrupt their interlocutors more frequently. The findings, based on our samples, also suggest that speaking a foreign language (as we can notice in the German-Polish pairs) usually means less competitive speaking, as well as fewer segments and turn-takings.